(untitled) (Innovate Conferences, 2025)
This article explores the integration of environmental norms into international economic law, focusing on recent developments at the World Trade Organization (WTO) and beyond. It highlights the tension between trade liberalization and environmental protection, tracing the evolution of legal frameworks such as the WTO’s Fisheries Subsidies Agreement and the European Union’s Carbon Border Adjustment Mechanism. The article examines how international trade and investment agreements are increasingly embedding sustainability goals and reflects on the challenges and opportunities presented by this shift. In conclusion, it argues for a more coherent and sustainable global economic legal framework.